A study on the role of counselling service and follow-up in the use of family planning methods - (:unkn) unknown (My University, 2001)
Objective: The present study aimed to evaluate the effectiveness of counselling service and follow-up procedure for family planning in two suburban areas of the Küçübkçekmece Health Education and Research District in Istanbul. Methods: Midwives were trained in family planning by physicians. Ten women for case and 10 women for control groups were chosen for each midwife from the follow up records of fertile women, and 455 women in total who did not use any family planning methods were chosen for case and control groups. The groups were followed up monthly, as case groups were given counselling service on family planning. Control groups received only routine health service. The attitudes of women in all groups were followed for two years. Then the program was extended to the whole district, and data related to the use of family planning methods for the last five years was evaluated. Results: Sixty seven point four percent of the women in the case groups and 43.4% of the control groups began using family planning methods when the program ended. The rate increased up to 78% for the following years and then saturated. Conclusion: The women in the district were put in touch with family planning users, and the use of family planning methods increased. For the use of modern family planning methods more efficiently in the community, the methods should be offered free of charge and counselling service should work in harmonious coordination.
Keywords: Counselling service; Family planning; Family planning methods